MYOC Gene Sequencing Analysis in Primary Open-Angle Glaucoma Patients from the Centre Region of Portugal - Silva, Filipe (2021)
Primary open-angle glaucoma is the most frequent subtype of glaucoma. Relatives of primary open-angle glaucoma patients have an increased risk of developing the disease, suggesting a genetic predisposition to the disease. MYOC was the first primary open-angle glaucoma-causing gene identified. This study aimed to identify sequence variations in the MYOC gene that may be responsible for the phenotype in a group of primary open-angle glaucoma patients from the Centre Region of Portugal.